Film Animasi sebagai Sarana Penguatan Karakter dan Kesadaran Lingkungan Anak Usia Sekolah Dasar Jari 2 - Indriani, Yulia; Ainurrochimah, Hany Ica; Lukita Cahyani, Tiara Rizqy; Tunggal Dewi, Tahta Tribuana; Bilqinaristi, Chairissa (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aims to strengthen character and environmental awareness among elementary school children through educational animated films. The activity was carried out at JARI 2 Elementary School, involving fourth and fifth-grade students as the main participants. The method included screening of animation films with character-building and environmental themes, interactive discussions, and reflective activities through drawing and storytelling. The selected films were chosen based on their moral values, environmental messages, and age-appropriateness. The results indicate that animated films successfully captured students’ attention, facilitated understanding of values such as responsibility, cooperation, and environmental care, and encouraged positive behavioral changes in daily life. Furthermore, there was a noticeable increase in students' active participation in maintaining school cleanliness and environmental preservation. This activity demonstrates that enjoyable and meaningful visual media can serve as an effective tool for early character education and environmental awareness.